Speaking Skill Guru dalam Pembelajaran Menurut Al-Quran - Adi Kasman (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2022)
Speaking skill is one of the communication skills. A good teacher must have the ability to communicate effectively, empathically, and politely. The communication skills of a teacher will determine the success of the previously designed program. With good speaking skills and techniques, a teacher can convey information clearly in front of students. The key to speaking skills is how a person can speak well and structure so that the ideas he wants to convey can be easily understood by many people. Speaking skills are not only how to speak but also must be accompanied by body language, self-confidence, confidence, and a good demeanor to make the audience feel comfortable. A teacher who has to deliver subject matter every day or deliver educational messages to students can be categorized as a good speaker teacher. With good speaking skills, teachers can more easily deal with unexpected situations. In addition, the importance of speaking skills for teachers is that all material and information conveyed to students will be easier to understand and well received.